Cold‐adapted Bacilli isolated from the Qinghai–Tibetan Plateau are able to promote plant growth in extreme environments. (5th August 2019) - Wu, Huijun; Gu, Qin; Xie, Yongli; Lou, Zhiying; Xue, Pengqi; Fang, Liu; Yu, Chenjie; Jia, Dandan; Huang, Guochao; Zhu, Bichun; Schneider, Andy; Blom, Jochen; et al.
Summary: Nearly 1400 Bacillus strains growing in the plant rhizosphere were sampled from different sites on the Qinghai–Tibetan Plateau. Forty‐five of the isolates, selected due to their biocontrol activity, were genome‐sequenced and their taxonomic identification revealed that they were representatives of the Bacillus subtilis species complex (20) and the Bacillus cereus group (9). Majority of the remaining strains were found closely related to Bacillus pumilus, but their average nucleotide identity based on BLAST and electronic DNA/DNA hybridization values excluded closer taxonomic identification. A total of 45 different gene clusters involved in synthesis of secondary metabolites were detected by mining the genomes of the 45 selected strains. Except eight mesophilic strains, the 37 remaining strains were found either cold‐adapted or psychrophilic, able to propagate at 10°C and below ( Bacillus wiedmannii NMSL88 and Bacillus sp. RJGP41). Pot experiments performed at 10°C with winter wheat seedlings revealed that cold‐adapted representatives of B. pumilus, B. safensis and B. atrophaeus promoted growth of the seedlings under cold conditions, suggesting that these bacilli isolated from a cold environment are promising candidates for developing of bioformulations useful for application in sustainable agriculture under environmental conditions unfavourable for the mesophilic bacteria presently in use.